Выбор абсорбентов для очистки сбросных газов содового производства от сероводорода - Анопа, Антон Станиславович; Райко, Валентина Федоровна (Національний університет "Львівська політехніка", 2017)
Среди жидкостей, имеющихся в технологическом цикле производства кальцинированной соды, как перспективные абсорбенты для очистки сбросных газов от сероводорода была выбрана жидкость, содержащая карбонат натрия и аммиак, и раствор карбоната натрия в насыщенном растворе хлорида натрия. Показано, что по совокупности свойств, таких как скорость абсорбции, емкость по поглощаемому компоненту и селективность, содосоляной раствор является наиболее подходящим.

Among the liquids available in the technological cycle for the production of soda ash, liquid containing sodium carbonate and ammonia and a solution of sodium carbonate in a saturated solution of sodium chloride were chosen as promising absorbents for purifying exhaust gases from hydrogen sulfide. It has been shown that in terms of a combination of properties, such as absorption rate, absorbent component capacity and selectivity, a soda-saline solution is most suitable.
The choice of absorbents for the purification of waste gases from soda production from hydrogen sulfide
Keywords: абсорбент; сбросные газы; содовое производство; сероводород